The Utilization of Artificial Intelligence by Commercial Banks and Its Effect on Accounting Disclosure in Compliance with Transparency Mandates: Evidence from the Iraqi Stock Exchange - Al-Dulaimi, Khitam Raheem Sabr; Ameen, Iman Baqer; Wahhab, Asaad (Technium Social Sciences Journal, 2025)
Artificial intelligence (AI) has emerged as a significant development in the accounting sector in recent years, with extensive ramifications across many fields, including business. Consequently, accounting scholars and professionals must stay abreast of this progress to identify present and future solutions to challenges that accountants and auditors in the corporate sector may face due to these applications. The current study aims to investigate the type of artificial intelligence (AI) applications in Iraqi commercial banks listed on the Iraq Stock Exchange, their impact on accounting disclosure, and their adherence to transparency rules. A questionnaire was created with four major sections: demographic data, evaluation of AI applications and transparency requirements, and the extent to which disclosure in these banks meets international transparency criteria. To collect credible data on the use of AI in the Iraqi banking sector, a questionnaire was issued to 191 participants, including accountants, internal auditors, academics, and financial professionals. Descriptive statistics were employed to assess the validity and reliability of the demographic data. The study hypotheses were based on simple and multiple linear regression with the least squares approach. The study found that there is a 53% correlation between the utilization of artificial intelligence and accounting disclosure. In comparison, the correlation premium for transparency standards was 60.6%, with a statistical significance of 0.00. Most Iraqi banks in the study sample use artificial intelligence systems, which improve the quality and openness of financial reporting. Furthermore, Iraqi banks are dedicated to transparency norms to some degree. The rulings underline the need for regulatory structures and procedures that permit the widespread use of contemporary technology to create transparency and financial sustainability, hence increasing investor and stakeholder confidence in the Iraqi financial market.